A Feasibility Study on the Establishment of Fructus Cupcake in Banlat Road, Quezon City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
This proposed business, to be located at Banlat Road, Tandang Sora near subdivision, roads, villages and schools, Fructus Cupcake will offer a variety of fruit cupcakes. The researchers conducted a survey and food tasting with 100 selected students aged 15 years old and above. Interviews were also done. Results show that avocado is the flavor chosen by majority of the respondents. 75 percent are willing to spend Php 100.00 for a piece of cupcake. 65 percent claim to visit a store twice a month craving for cupcakes. The marketing viability of Fructus Cupcake is based on the surveys conducted by the researchers. Obviously, the customers patronize variety of flavors of cupcakes as they are new to their taste and for a healthy living. Strong marketing campaign will be implemented. In financial aspect, we found out that the net sales can increase by 13 percent per year and the cost of sales increase is projected at thirteen percent each year parallel to the net sales with additional inflation rate of 2.5 percent. The researchers conclude that business Fructus Cupcake can be profitable based on the financial aspects conducted.
Keywords: home-made, fruity flavors, cupcake, communication skills, net sales